Implementation of Ciprat Batik Training for Disabled Peoples as Economic Empowerment Efforts - Rahmawati, Rahmawati; Purnomo, Rochmat Aldy; Rudianto, M; Amperawati, Endang Dwi (IMPOWERMENT SOCIETY, 2024)
There is a very dreadful problem with unemployment, especially in an educated person. The availability of sufficient jobs does not match the high number of employees. Such conditions need to be remedied in order not to increase unemployment. In addition to the growing number of graduates, a lack of initiative to open one's jobs or become entrepreneurs also played a role. The aims and goals are to understand how to learn entrepreneurship in an entrepreneurial program that can transform disabled people's attitude into effective business people with a higher education curriculum. This method uses a qualitative and intense approach, namely, to provide entrepreneurial and mentoring education to disabled people through teachers, practitioners, and all parties involved. This service is carried out by the facts and properties of the object systematically, factually, and accurately. The result of this community service activity is the training in Kampung Idiot Ponorogo of the mentality of the people with disabilities. Thus, it is necessary to have a format or a road map in the idiot village of Ponorogo to achieve the efficiency of the ciprat batik learning program.